The Association of Periodontitis With Risk of Prevalent and Incident Metabolic Syndrome - Kinnunen, Jenni; Koponen, Kari; Kambur, Oleg; Manzoor, Muhammed; Aarnisalo, Katariina; Nissilä, Verneri; Männistö, Satu; Salomaa, Veikko; Jousilahti, Pekka; Könönen, Eija; Gürsoy, Ulvi Kahraman; Havulinna, Aki S.; et al. (Wiley-Blackwell, 2026)
Aim
To investigate whether periodontitis is associated with prevalent and incident metabolic syndrome (MetS).
Materials and Methods
The baseline study included 4183 individuals from a population-based survey (DILGOM) in 2007 and follow-up of 1047 participants with clinical re-examination in 2014. The risk of periodontitis was assessed with saliva biomarkers using a validated, three-group cumulative risk score for periodontitis (CRS I, II and III).
Results
In fully adjusted models, CRS III was associated with prevalent MetS (OR: 1.35, 95% CI [1.11–1.65]), high waist circumference (1.55 95% CI [1.26–1.91]), high blood pressure (1.29 95% CI [1.05–1.59]) and the number of MetS components (β: 0.18, 95% CI [0.06–0.30]). Among participants without MetS at baseline (n = 618), 128 (20.7%) developed MetS during follow-up. In the fully adjusted model, CRS III trended positively with incident MetS (RR: 1.55, 95% CI [ 0.96–2.51]) in the whole population and had a significant positive association in women (2.06, 95% CI [1.08–3.94]), and in non-smokers (1.78, 95% CI [1.01–3.14]). The risk between CRS and incident MetS was mediated via systemic inflammation.
Conclusion
Periodontitis is associated with an increased risk of having metabolic syndrome and, in particular, clearly with the number of MetS components: abdominal obesity, hyperglycaemia and hypertension. Systemic inflammation may elucidate the observed higher risk of incident MetS.